Development Of The Spatial Intelligence Of Teenagers - Nseif Inad, Sheima (Opción, 2019)
The sample of the study consisted of (102) male and female adolescents in the ages (13,15,17). They were selected by random stratification method. To achieve the research objectives, a 5-point test was applied. 1. Adolescents (13,15,17) have spatial intelligence. 2. Spatial intelligence The ability of the flu- id deteriorates with age in adolescence 3 - influenced by the intelligence of age and age (13,15) years, respectively. 4 - Spatial intelligence is not affected by sex (males, females) in ages (13,15) years. 5 - is influenced by the spatial intel- ligence sex at the age (13). 6 - is not affected by spatial intelligence specializa- tion (scientific, literary). In the light of the conclusions reached, the researcher made a number of recommendations and suggestions. 1- The development of spatial intelligence in adolescents in the ages (13,15,17) years. 2 - Significance of differences in spatial intelligence according to the variable age (13,15,17) years. 3 - Significance of differences in spatial intelligence in adolescents age (13) years, depending on the sex variable (males, females). 4 - Significance of differences in spatial intelligence in adolescents (15,17) years according to var- iables: - Sex (males, females). - Academic specialization (scientific, literary).